Hak Cipta Dalam Sudut Pandang Nilai – Nilai Pancasila - Muhammad Rifqi Fauzi (JIPRO: Journal of Intellectual Property, 2020)
Hak Cipta is a legal protection for authors interest to protect their works, particularly for science, art and literature works. Indonesia has great potency for science, art and literature works. For that reason, it is important for Indonesia to protect those works. In this world, the protection of science, art and literature works is divided into two systems which are Author’s Right system and Copyright system. Author's right system recognizes moral right and economic right. On the other hand, Copyright system doesn't recognize moral right. This paper is intended to explain whether Hak Cipta protection in Indonesia to use Author’s Right system or Copyright system through the discussion of regulations on Hak.Cipta that ever applied in Indonesia. Those regulations will be seen from the point of view of Pancasila as the nation ideology and Staatsfundamentalnorm. The research method used is normative juridical approach with qualitative method and descriptive data analysis. The conclusion of the research is stated that Indonesia to use Author’s Right System. It is because from Auteurswet 1912 until Act No. 28 of 2014 on Hak Cipta regulate moral right and economic right as part of Hak Cipta. From the point of view of Pancasila, Author’s Right System is in accordance with five values contained in Pancasila.Keywords : Hak Cipta, Author’s Right, Copyright and Pancasila.